Reasons behind low achievement in English language for Tawjihi students and suggested remedies - QALALWI, NOOR NAYEF (The journal of contemporary issues in business and government, 2021)
This study aimed at investigating the reasons for the English low achievement level among the second secondary students in Qabatya district schools, and suggested remedies tackling this weakness. The questions of the research were: Who stood behind the low achievement in English language that faces Tawjihi students as perceived by English teachers and students in Qabatya district (teacher or student)? Were there any significant differences in Reasons behind low achievement in English language for Tawjihi students as perceived by the teachers due to (gender, qualification and experience)? Were there any significant differences in Reasons behind low achievement in English language for Tawjihi students as perceived by the students due to (gender and stream)? In order to fulfill the objectives of this study; the researcher used a cross-sectional design based on questionnaires distributed. 63 questionnaire items were set to identify the reasons for the low English achievement level among the secondary school students in Qabatya district. This study targeted English language teachers and Tawjihi students in Qabatya district to measure Reasons behind low achievement in English language scores for Tawjihi students and suggested remedies. The results of the questionnaire showed that: - Teachers thought that the main reason for low achievement in English language according to the items in the teacher questionnaire are related to “Students not well constructed in English language from the beginning”. This item received an 89.33% of the English language teachers’ agreement. In addition, teachers considered English language classes’ quantity is not enough as a second main reason for low achievement for Tawjihi students. This statement received 89.63%. Other important factors for low achievement which also received a high degree of agreement include “Students only care to pass the Tawjihi English exam” and “Students dislike English language”. On the other hand, Tawjihi students that their low achievement in English is because their Parents ignore their low grades in English, the teachers lack proficiency and Teachers mostly use mother tongue in the class. These Were the most important reasons for their low achievement. There were no statistically significant differences in means that at (p value = 0.05) in Reasons behind low achievement in English language for Tawjihi students due to academic qualification for the teachers, experience and gender. There were no statistically significant differences in means that at (p value = 0.05) in Reasons behind low achievement in English language for Tawjihi students from Tawjihi students perceptive due to stream and gender. The researcher suggested an instructional program for tackling this weakness and gives relevant recommendations. The most significant were: English language teachers should attend training courses before entering the class for the first It is strongly recommended that low achieving students should attend classes away from others with different content material. Schools should be fixed to suit the curriculum demands and the students’ age ??? It is necessary to add two more English periods to the weekly English